The Relationship between Academic History and Audio-Visual History in Lithuania: A Closing of the Gap? - Rūta Šermukšnytė (Lietuvos Istorijos Studijos)
The article is aimed at enumerating the barriers to cooperation between audio-visual communications specialists and formal historians in Lithuania in the 1988-2005 period, determining preconditions for overcoming these stumbling blocks and demonstrating the gap between these two spheres plus the consequences of its narrowing for audio-visual work. Documentary films and documentary-type cultural programs in which recognizable historical reports are discernible and which were made in the 1988-2005 period were used to achieve these aims.